The tuxedo [videorecording (Blu-Ray)] - Cheng, Long, 1954-; Hewitt, Jennifer Love, 1979-; Isaacs, Jason, 1963-; Mazar, Debi; Stormare, Peter; Donovan, Kevin (Paramount Pictures, 2024)
Mild-mannered chauffeur Jimmy Tong leads an unexciting life until he learns that his wealthy boss is really a spy and that his employer's tuxedo is actually a top-secret spy gadget. Jimmy tries on the tuxedo and is thrust into a world of international espionage.